Waste Valorization for Value-added Products - Kumar, Vinay; Krishna Lakkaboyana, Sivarama; Sharma, Neha (Bentham Science Publishers, 2023)
This volume is a comprehensive compilation of reviews that show how various waste products can be used to produce useful products. Thirteen chapters highlight the following topics:- applications of plant-derived and fruit waste for value-added product formation;- fuel and chemical production from lignin- food waste bioconversion to high-value products- organic residues valorization for value-added chemicals- valorization of waste plastics to produce fuels and chemicals- food valorization for bioplastic production and concepts of circular economy in the valorization process.Chapters are written in an organized and strategic manner and also include the references from recent years. It will help students and researchers to quickly learn about modern waste valorization practices and advance their knowledge on the subject. The book is suitable as a reference for courses in environmental science, chemical engineering and agriculture. It also serves as a guide for trainees, managers and readers involved in waste management, sustainability and value-added product supply chains